ECONOMIC GROWTH AND EQUITY PERSPEKTIF EKONOMI SYARIAH - Istianah Istianah (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2022)
Economical concepts and policies based on capitalism and socialism have proven to have failed to create a just economy. This is caused adhering to capitalist and socialist ideologies, macroeconomic imbalances and national instability occur. So far, the capitalist and socialist economic system is clearly incompatible with the Islamic value system. Both are more exploitative and unfair in treating humans not as humans. Both systems are also unable to respond to the economic, political, social and moral challenges of today's era. This is not only because there are ideological differences, moral attitudes and socio-political frameworks, but also for reasons that are more worldly economic in nature, resource differences, changing international economic situations, respective economic levels and high socio-economic costs of development. (high cost economist). Therefore, it is urgent to review how the concept of economic growth and equity according to Islam can be a solution for the creation of community economic justice. This research methodology uses a qualitative approach with an interpretation pattern of developing ideas through data collection techniques from participant observation, interviews, and directed discussions. So, it can be help maximally of the economic problems development in Indonesia.